(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
This paper serves as a preliminary presentation of an existential family therapy approach. It is based on presentation delivered at the Fifth European Conference for Existential Therapy, held in Istanbul on May 2024. Existential family therapy is a therapeutic approach that aims to integrate existential psychotherapy with foundational principles of family therapy. It is a work in progress with important implications for clinical practice and future research.